Optical Coherence Tomography Angiography Biomarkers of Retinal Thickness and Microvascular Alterations in Sjogren's Syndrome - Liu, Ren; Wang, Yan; Li, Qiuyu; Xia, Qiang; Xu, Tian; Han, Ting; Cai, Shuang; Luo, Shuilin; Wu, Rui; Shao, Yi (Frontiers in Neurology, 2022)
Purpose: To investigate the differences of retinal thickness (RT) and superficial vascular density (SVD) between patients with Sjogren’s syndrome (SS) and healthy controls (HCs) using optical coherence tomography angiography (OCTA). Methods: Individuals with SS and healthy controls were enrolled (n=12 per group). An en-face OCTA scan was performed on each eye. Images were segmented into 9 subregions and macular retinal thickness (RT) and superficial vessel density (SVD) were measured and compared between the 2 groups. Results: Visual acuity (VA) differed significantly between SS patients (24 eyes) and controls (24 eyes) (P<0.001). In SS patients, inner RT was reduced in the inner superior region, outer RT was reduced in the outer nasal (ON) region, and full RT was reduced in the ON region compared to the control group (P<0.05). RT was negatively correlated with serum IgG level in the outer and full retina at ON regions (P < 0.05). SVD in the inner nasal, ON, and inner temporal regions was significantly lower in SS patients than in control subjects (P<0.05). SVD was positively correlated with full RT in the ON region in SS patients (P<0.05). The areas under the receiver operating characteristic curves for the diagnostic sensitivity of outer RT and full RT in the ON region for SS were 0.828 (95% confidence interval [CI]: 0.709–0.947) and 0.839 (95% CI: 0.715–0.963), respectively. Conclusions: In SS patients, retinal thinning in the macular area—which affects vision—can also reflect the severity of dry eyes in SS and has clinical value for assisted imaging diagnosis.